Risk factors of in-home unintentional injuries among 0-6-year-old children in Changsha city of China: a cross-sectional survey based on Bronfenbrenner's ecological system theory - Yihan Ma; Juan Song; Ming Hu; Rusi Yang; Panzi Yang (BMC, 2022)
Abstract Background In-home unintentional injuries (IUIs) seriously threatened children's safety. Three factors, including risky behaviors, parental supervision, and home environmental risks, have been identified as major causes for IUIs. Studies considering the interrelations between the three were limited and no relative studies has been carried out among Chinese children. The purpose of this study is to fully explore the influences of behavioral, supervisory and environmental risk factors on IUIs and their associations among Chinese children on the bases of our self-developed scales. Methods Through stratified cluster sampling, a cross-sectional survey was conducted with 798 parents of children aged 0 ~ 6 years in Changsha, China. Social demographics and IUIs history in the past year were collected by self-administered questionnaires. Three IUI-related scales, which had been developed and validated by our team, aimed to measure risks from children behavior, parental supervision and in-home environment. Structural equation models were constructed to analyze the relationship of these factors and their influences on IUIs using SPSS 26.0 and AMOS 22.0. Results Seven hundred ninety-eight parents were surveyed in total, and 33.58% of them reported with IUIs history of their children. X 2/df, goodness-of-fit index (GFI), adjusted goodness-of-fit index (AGFI) and the root-mean-square error of approximation (RMSEA) for the model of the whole children were 4.832, 0.879, 0.856 and 0.069 respectively, indicating an acceptable level of model fit. Direct influences were discovered between risky behaviors and children's IUIs. Home environmental risks indirectly exerted impacts on IUIs by the mediating effect of risky behaviors, while the significant effect of parental supervision only existed in children aged 4-6 and girls. Conclusions Risky behaviors played a mediating role in IUIs among children. Supervision and environmental risks affected IUIs indirectly by the exposure to risky behaviors. Parental supervision may not be able to offset the risks posed by the environmental and behavioral factors, so effective IUIs prevention strategies should focus on behavioral and environmental interventions, with appropriate supervision strategies based on the age and sex characteristics of the child.